Effect of Cell Spreading on Rosette Formation by Human Pluripotent Stem Cell-Derived Neural Progenitor Cells - Townshend, Ryan F.; Shao, Yue; Wang, Sicong; Cortez, Chari L.; Esfahani, Sajedeh Nasr; Spence, Jason R.; O’Shea, K. Sue; Fu, Jianping; Gumucio, Deborah L.; Taniguchi, Kenichiro (Frontiers in Cell and Developmental Biology, 2020)
Neural rosettes (NPC rosettes) are radially arranged groups of cells surrounding a central lumen that arise stochastically in monolayer cultures of human pluripotent stem cell (hPSC)-derived neural progenitor cells (NPC). Since NPC rosette formation is thought to mimic cell behavior in the early neural tube, these rosettes represent important in vitro models for the study of neural tube morphogenesis. However, using current protocols, NPC rosette formation is not synchronized and results are inconsistent among different hPSC lines, hindering quantitative mechanistic analyses and challenging live cell imaging. Here, we report a rapid and robust protocol to induce rosette formation within six hours after evenly-sized “colonies” of NPC are generated through physical cutting of uniformly polarized NESTIN+/PAX6+/PAX3+/DACH1+ NPC monolayers. These NPC rosettes show apically polarized lumens studded with primary cilia. Using this assay, we demonstrate reduced lumenal size in the absence of PODXL, an important apical determinant recently identified as a candidate gene for juvenile Parkinsonism. Interestingly, time lapse imaging reveals that, in addition to radial organization and apical lumen formation, cells within cut NPC colonies initiate rapid basally-driven spreading. Further, using chemical, genetic and biomechanical tools, we show that NPC rosette morphogenesis requires this basal spreading activity and that spreading is tightly regulated by Rho/ROCK signaling. This robust and quantitative NPC rosette platform provides a sensitive system for the further investigation of cellular and molecular mechanisms underlying NPC rosette morphogenesis.